Pedobacter lusitanus sp. nov., isolated from sludge of a deactivated uranium mine - Covas, Cláudia (2018)
Strain NL19(T) is a Gram-stain-negative, aerobic bacterium that was isolated from sludge of a deactivated uranium mine in Portugal. 16S rRNA gene sequence analysis revealed that strain NL19(T) is a member of the genus Pedobacter and closely related to the strains Pedobacter himalayensis MTCC 6384(T), Pedobacter cryoconitis DSM 14825(T), Pedobacter westerhofensis DSM 19036 (T) and Pedobacter hartonius DSM 19033(T). It had a DNA G+C content of 40.8 mol%, which agreed with the genus description. The main fatty acids included C-16 : 1 omega 7c, C-14 : 1 omega 5c, C-4 : 0, iso-C-17 : 0, iso-C-17 : 0 3-OH, C-16 : 0, anteiso-C-15 : 0 and isoC(15 : 0) 3-OH. The main lipids present were phospholipids (60 %) and sphingolipids (35 %). The most abundant phospholipids included phosphatidylethanolamine, phosphatidylinositol and phosphatidylcholine. Menaquinone-7 (MK-7) was the only isoprenoid quinone detected. DNA-DNA hybridization similarities between strain NL19(T) and Pedobacter himalayensis MTCC 6384(T), Pedobacter cryoconitis DSM 14825(T), Pedobacter westerhofensis DSM 19036(T) and Pedobacter hartonius DSM 19033(T) were 15.3, 16.2, 11.5 and 16.0 %, respectively. Strain NL19(T) can also be distinguished from these four species based on gyrB and intergenic transcribed spacers (ITS) sequences and by some phenotypic traits such as NaCl tolerance, pH, growth temperature and carbon source utilization. Strain NL19(T) represents a novel species of the genus Pedobacter, for which the name Pedobacter lusitanus sp. nov. is proposed. The type strain is NL19(T) (= LMG 29220(T) = CECT 9028(T)). An amended description of Pedobacter himalayensis is also included.